Evaluation of beam-column joints made of HPFRCC composites to reduce transverse reinforcements. (15th December 2019) - Nouri, Abolfazl; Saghafi, Mohammad Hossein; Golafshar, Ali
Highlights: Four half-scale exterior beam-column connections are tested under cyclic loads. The use of HPFRCC materials may result in reduced transverse reinforcement. Flexural failure was observed at failure stage of HPFRCC beam–column joint. Abstract: In reinforced concrete frames with high ductility, due to the large amount of transverse reinforcement in the beam-column joints, reinforcement concentration induces problems in the construction and concreting. In order to prevent the reinforcement concentration and to reduce the amount of transverse reinforcement in the joints, high performance fiber reinforced cementitious composites (HPFRCC) are used with 2% steel fibers. The mechanical properties of HPFRCC materials are determined by uniaxial compressive and tensile tests. In order to evaluate the shear improvement effects of HPFRCC, four joint specimens have been made including a normal concrete control specimen designed according to special seismic provision requirements and three joints with HPFRCC materials with different transverse reinforcement spacing intervals in beam, column and without transverse reinforcement in the joint zone. The specimens have been tested under cyclic load. The results show that the use of HPFRCC materials in joints can be a good solution to reduce the amount of transverse reinforcements and damage index and increase of the load-carrying capacity, energy dissipation, damping percentage and stiffness of members. Moreover, the behavior of the HPFRCC joints is independent of the distance between the transverse reinforcement in the beams and columns, and in all of these specimens, the behavior has been improved compared with that of the control specimen.